2006
DOI: 10.1049/ip-syb:20060009
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of ATP synthase to stimulation of respiration by Ca2+ in heart mitochondria

Abstract: A variety of experimental conditions were applied with the aim to estimate the correlation between the contribution of ATP synthase to the respiratory flux control and the calcium-induced activation of succinate oxidation in heart mitochondria isolated from rat, rabbit and guinea pig. The sensitivity of respiration in heart mitochondria to the decrease in temperature from 37 degrees C to 28 degrees C decreases in the order rabbit > guinea pig > rat. Ca2+ effect on succinate oxidation rate in state 3 respiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…7B has a slope that is lower compared with the data in Fig. 3 (A and B) (5) showed that the cardiac mitochondrial respiratory response in the rat has a low calcium sensitivity with succinate as a substrate compared with rabbit and guinea pig. Similarly, the low Ca 2ϩ sensitivity of mitochondrial respiration and NAD(P)H fraction with pyruvate/malate observed in our study could potentially be species-specific.…”
Section: Data Analysis and Characterization Of Nad(p)h Transient Shapmentioning
confidence: 62%
See 2 more Smart Citations
“…7B has a slope that is lower compared with the data in Fig. 3 (A and B) (5) showed that the cardiac mitochondrial respiratory response in the rat has a low calcium sensitivity with succinate as a substrate compared with rabbit and guinea pig. Similarly, the low Ca 2ϩ sensitivity of mitochondrial respiration and NAD(P)H fraction with pyruvate/malate observed in our study could potentially be species-specific.…”
Section: Data Analysis and Characterization Of Nad(p)h Transient Shapmentioning
confidence: 62%
“…The results plotted in Fig. 7 (A (respiration) and B (redox versus respiration)) show that respiration was stimulated from 0 to 100 nM Ca The effect of Ca 2ϩ on the respiration and redox responses of cardiac mitochondria has been found to be dependent on the substrates used, the species of the animal, and the experiment temperature (5,6,19,21). The cited studies reported that the stimulatory effect of Ca 2ϩ on State 3 mitochondrial respiration with pyruvate/malate was between 20 and 30%; therefore, subsaturating 2-oxoglutarate or saturating glutamate and malate were used as substrates to demonstrate Ca 2ϩ stimulation of mitochondrial State 3 respiration.…”
Section: Data Analysis and Characterization Of Nad(p)h Transient Shapmentioning
confidence: 98%
See 1 more Smart Citation
“…Ca 2+ can affect ATP supply by stimulating PDH activity and other dehydrogenase mechanisms, such as isocitrate and α-ketoglutarate (reviewed in [69]). Whether Ca 2+ directly activates ANT remains controversial [70]. It has also been reported that an increase in mitochondrial Ca 2+ level can regulate mitochondrial matrix volume [71] which in turn can elevate respiration in isolated mitochondria suspensions.…”
Section: Direct and Indirect Regulatory Control Mechanisms To Match Ementioning
confidence: 99%
“…However, synthesis of ATPase cannot compensate for extra energy consumption following chronic alcohol intake. Down-regulated expression of ATPase mRNA and protein, corresponding to transcription and post-transcriptional regulation, elicits alteration of enzymatic structure and loss of enzyme content [3032]. These changes in structure and content of enzyme may lead to cellular energy deficiency.…”
Section: Discussionmentioning
confidence: 99%